1990
DOI: 10.1159/000248046
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Necrotizing Purpura

Abstract: A 30-year-old woman with recurrent necrotizing purpura on the legs which did not fit, to our knowledge, within any distinctive pathological entity, is described. Laboratory investigations disclosed a mild thrombocytopenia and antiphospholipid antibodies, i.e. lupus anticoagulant and anticardiolipin. Cutaneous lesions maybe an early marker of the antiphospholipid antibody syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Post‐phlebitic ulcers were observed in patients with recurrent phlebitis of the leg, after many years of followup. In contrast, circumscribed skin necrosis is frequently an early feature of APS, often preceded by necrotizing purpura (22, 23). In a series of 21 consecutive patients with atrophie blanche–like ulcers or livedoid vasculitis, aPL were detected in 4 (19%), of whom 1 had SLE‐related APS and 3 had primary APS (24).…”
Section: Discussionmentioning
confidence: 99%
“…Post‐phlebitic ulcers were observed in patients with recurrent phlebitis of the leg, after many years of followup. In contrast, circumscribed skin necrosis is frequently an early feature of APS, often preceded by necrotizing purpura (22, 23). In a series of 21 consecutive patients with atrophie blanche–like ulcers or livedoid vasculitis, aPL were detected in 4 (19%), of whom 1 had SLE‐related APS and 3 had primary APS (24).…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing purpura may precede livedoid vasculitis-like ulcers by years. 50,51 This term has been applied to a form of cutaneous necrosis.…”
Section: Dermatologic Findingsmentioning
confidence: 99%
“…The most frequent cutaneous manifestation was spontaneous thrombophlebitis syndrome (34%), followed by skin ulcer (30%), gangrene (19%), haemorrhage (14%) and cutaneous necrosis (3%). Some authors have reported isolated cases of rare cutaneous changes associated with APS such as necrotizing vasculitis, 19 livedoid vasculitis 20 or cutaneous nodules. 5,6 A small papule or a subcutaneous nodule emerged as a cutaneous manifestation of APS in four patients in our series.…”
Section: Discussionmentioning
confidence: 99%